Towards Macroprudential Stress Testing : Incorporating Macro-Feedback Effects - Krznar, Ivo (IMF Working Papers; Working Paper, 2017)
Macro-feedback effects have been identified as a key missing element for more effective macro-prudential stress testing. To fill this gap, this paper develops a framework that facilitates the analysis of both the direct effects of macroeconomic shocks on the solvency of individual banks and feedback effects that allow for the amplification and propagation of shocks that can result from bank deleveraging and credit crunches. The framework ensures consistency in the key relationships between macroeconomic and financial variables, and banks' balance sheets. This is accomplished by embedding a standard stress-testing framework based on individual banks' data in a semi-structural macroeconomic model. The framework has numerous applications that can strengthen stress testing and macro financial analysis. Moreover, it provides an avenue for many extensions that address the challenges of incorporating other second-round effects important for comprehensive systemic risk analysis, such as interactions between solvency, liquidity and contagion risks. To this end, the paper presents some preliminary simulations of feedback effects arising from the link between the liquidity and solvency risk.